2000
DOI: 10.1016/s0896-6273(00)00101-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ethanol Tolerance in Drosophila

Abstract: In humans, repeated alcohol consumption leads to the development of tolerance, manifested as a reduced physiological and behavioral response to a particular dose of alcohol. Here we show that adult Drosophila develop tolerance to the sedating and motor-impairing effects of ethanol with kinetics of acquisition and dissipation that mimic those seen in mammals. Importantly, this tolerance is not caused by changes in ethanol absorption or metabolism. Rather, the development of tolerance requires the functional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
293
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(324 citation statements)
references
References 48 publications
(2 reference statements)
11
293
1
Order By: Relevance
“…Previous work by others has established Drosophila as a useful model organism for studies of ethanol (20), including the mechanisms of ethanol tolerance (23). Exposure to ethanol (C) dsRNA-II (as in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by others has established Drosophila as a useful model organism for studies of ethanol (20), including the mechanisms of ethanol tolerance (23). Exposure to ethanol (C) dsRNA-II (as in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their physiological function, the GABA B receptors may play a role in the behavioral actions of addictive compounds such as ethanol (16)(17)(18)(19). Although Drosophila has been used to study the mechanisms of action of alcohol (20)(21)(22)(23), as yet, this model has not been used to characterize the involvement of GABA B receptors. show high sequence homology to mammalian GABA B R1 and GABA B R2, respectively; the subunit D-GABA B R3 seems to be an insectspecific subtype with no known mammalian counterpart and no known function.…”
mentioning
confidence: 99%
“…The white gene is at 3B2-3C2 (Pirotta et al 1983) and is complemented by the Dp(1:Y)w+ chromosome based on eye color. The mini-white gene in the cantonized tetanus toxin light chain GAL4-UAS effector line CYO34-1 (Scholz et al 2000) was also tested for behavioral rescue of wCS13 mutant flies. Additionally, the bw 1 and st 1 mutations were outcrossed to wild-type flies for greater than six generations (Dreesen et al 1988;Tearle et al 1989).…”
Section: Genetic Manipulations and Culture Conditionsmentioning
confidence: 99%
“…Extensive studies of the neuroadaptations accompanying tolerance development have shown genetic influences to be strong (Kalant et al 1971;Kalant 1998). Recent studies using the powerful genetic manipulations available in invertebrate species have extended the range of genetic influences thought to be responsible (Scholz et al 2000;Cowmeadow et al 2005).…”
Section: Introductionmentioning
confidence: 99%